Recurrent and convolutional neural networks for sequential multispectral optoacoustic tomography (MSOT) imaging - Aniwat Juhong; Bo Li; Yifan Liu; Cheng‐You Yao; Chia‐Wei Yang; Dalen Agnew; Yu L. Lei; Gary D. Luker; Harvey L. Bumpers; Xuefei Huang; Wibool Piyawattanametha; Zhen Qiu (Journal of Biophotonics, 2023)
Multispectral optoacoustic tomography (MSOT) is a beneficial technique for diagnosing and analyzing biological samples since it provides meticulous details in anatomy and physiology. However, acquiring high through-plane resolution volumetric MSOT is time-consuming. Here, we propose a deep learning model based on hybrid recurrent and convolutional neural networks to generate sequential cross-sectional images for an MSOT system. This system provides three modalities (MSOT, ultrasound, and optoacoustic imaging of a specific exogenous contrast agent) in a single scan. This study used ICG-conjugated nanoworms particles (NWs-ICG) as the contrast agent. Instead of acquiring seven images with a step size of 0.1 mm, we can receive two images with a step size of 0.6 mm as input for the proposed deep learning model. The deep learning model can generate five other images with a step size of 0.1 mm between these two input images meaning we can reduce acquisition time by approximately 71%.
Keywords: Photoacoustic and Ultrasonic Imaging; Optical Imaging and Spectroscopy Techniques; Thermography and Photoacoustic Techniques